Research on the Digital Development Path of Rural Cultural Industry under the Background of Rural Revitalization - Lu, Mengxue; Ren, Yixue; Niu, Yihao; Chang, Menghan; Xu, Yifei (International Journal of Global Economics and Management, 2025)
The rural revitalization strategy provides opportunities for the digital transformation of rural cultural industry. Under the background of rural revitalization and cultural industry innovation, digital transformation can break through the traditional model and promote economic and cultural development. This article analyzes the current situation and problems of rural cultural industry digitalization, and discusses its development path in combination with data and cases. The study shows that strengthening digital infrastructure construction, promoting technology integration, and improving talent training mechanisms will contribute to the high-quality development of rural cultural industry and help rural revitalization.